An evaluation study on gamified online learning experiences and its acceptance among medical students - May Honey Ohn; Khin Maung Ohn (2020)
Objective: The successful application of gamification in different educational settings shows that the use of gamification in medical education may be an effective solution. Even though many studies have been conducted to investigate the efficacy of the integration of gamification to different education curriculums, few studies have examined the reactions, behaviors, and attitudes of learners toward the use of gamification in medical education. Hence, this study aimed to evaluate the medical students' learning experience and acceptance of the use of gamification for the delivery of electrocardiogram lessons.